พิพิธภัณฑ์กับคุณค่าด้านการศึกษาจากประสบการณ์ - มีศีล ฐิติพร (NAJUA: Architecture, Design and Built Environment, 2017)
เมื่อพิจารณาเป้าหมายหลักขององค์กรที่สนับสนุนด้านการศึกษาอย่างพิพิธภัณฑ์ สารที่พิพิธภัณฑ์ทั่วโลกสื่อออกมามักมุ่งหวังให้เกิดการเรียนรู้จากปรากฏการณ์ที่เกิดขึ้นในสังคมจากอดีตสู่ปัจจุบัน เพื่อเป็นส่วนหนึ่งในการออกแบบอนาคตของสังคมนั้นๆ ประเทศไทยก็ดูเหมือนจะเดินตามภาพลักษณ์ของพิพิธภัณฑ์ในประเทศอื่นๆ กล่าวคือ การเกิดขึ้นของพิพิธภัณฑ์และการหยิบยกเรื่องราวมาสื่อความหมายจากวัตถุทางความทรงจำ หรือมรดกทางภูมิปัญญา มักเป็นไปตามความต้องการสื่อสารจากมุมมองของคนทำงานพิพิธภัณฑ์ ซึ่งอาจไม่เข้าถึงสารที่ผู้ชมต้องการได้รับ อาจเรียกได้ว่าสมดุลระหว่างอุปทาน หรือความต้องการในการให้บริการ และอุปสงค์ หรือความต้องการในการรับบริการ ยังไม่เกิดขึ้นในงานพิพิธภัณฑ์ทั่วไปในประเทศไทย บทความนี้เป็นส่วนหนึ่งของวิทยานิพนธ์ปริญญาเอกหัวข้อ “มุมมองของคนไทยต่อหน้าที่ของพิพิธภัณฑ์” มีจุดประสงค์เพื่อ 1) นำเสนอมุมมองส่วนหนึ่งของผู้ชื่นชอบการชมพิพิธภัณฑ์และผู้ไม่ต้องการชมพิพิธภัณฑ์ และ 2) เชิญชวนให้ช่วยกันค้นหาว่า แท้จริงแล้ว พิพิธภัณฑ์ไทยสามารถตอบโจทย์การเป็นองค์กรสนับสนุนด้านการศึกษาและเรียนรู้จากประสบการณ์การมีส่วนร่วมของผู้ชมในรูปแบบใด 3) การสื่อความหมายในพิพิธภัณฑ์แสดงถึงการส่งคุณค่าแท้หรือคุณค่าเทียม (คุณค่าเสริม) ของการศึกษาสู่สังคมไทย Museum and Its Values of Education from Experiences Titiporn Meesil Ph.D. Program in Architectural Heritage Management and Tourism (International Program) Faculty of Architecture, Silpakorn University Museum as an educational institution, has the purpose of passing on knowledge from the past to the present so that society can set its path towards the future. In this respect, it appears that Thailand has taken the same direction as other countries. Museums have been set up and stories have unfolded through artifacts, objects and memorabilia that are reminders of past wisdoms. Such stories are, most of the time, interpretations from the point of view of museologists and may not always concur with what the visitors expect. In other words, the supply (which refers to providing services), and demand (which refers to using the services), are out of balance and inconsistent as far as museums in Thailand are concerned. This article is part of a dissertation on the topic of “Investigation of Thai People’s Perception towards Museums”. The objectives are: 1) to convey the opinions of those who appreciate visiting museums and those who do not, 2) invite readers to express opinions on how museums can best represent their role as educational institution, and 3) find out whether information conveyed in museums are of direct or indirect educational value.